Finite element study on modification of bracket base and its effects on bond strength - Tarulatha R. Shyagali; Deepak P. Bhayya; Chandralekha B. Urs; Shashikala Subramaniam (Dental Press Editora, 2015)
OBJECTIVE: This article aims to analyze the difference in stresses generated in the bracket-cement-tooth system by means of a peel load in single and double-mesh bracket bases using a three-dimensional finite element computer model. MATERIAL AND METHODS: A three-dimensional finite element model of the bracket-cement-tooth system was constructed and consisted of 40,536 bonds and 49,201 finite elements using a commercial mesh generating programmer (ANSYS 7.0). Both single and double-mesh bracket bases were modified by varying the diameter from 100-400 µm progressively, and the spacing between the mesh wires was kept at 300 µm for each diameter of wire. A peel load was applied on the model to study the stresses generated in different layers. RESULTS: In case of double-mesh bracket base, there was reduction in stress generation at the enamel in comparison to single-mesh bracket base. There was no difference in stress generated at the bracket layer between single and double-mesh bracket bases. At the impregnated wire mesh (IWM), layer stresses increased as the wire diameter of the mesh increased. CONCLUSION: Results show that bracket design modification can improve bonding abilities and simultaneously reduce enamel damage while debonding. These facts may be used in bringing about the new innovative bracket designs for clinical use.